Structural revisions of the reported A-ring phosphine oxide synthon for ED-71 (Eldecalcitol) and a new synthesis. Issue 42 (21st October 2015) - Zhao, Guo-Dong; Liu, Zhao-Peng
Abstract: In a reported procedure for the synthesis of the ED-71 A-ring phosphine oxide, we discovered that unusual TBS transfer occurred from the 1α-position to the sterically more constrained 2β-position, and the subsequent Michael addition of ethyl acrylate predominated at the 1α-position. The X-ray analysis of a key intermediate confirmed our observations. We made a structural revision of the reported A-ring phosphine oxide synthon and ED-71. In addition, we provided the first stereoselective synthetic approach to ED-71 A-ring phosphine oxide applying the stereochemistry of d -mannitol. Graphical abstract: The reported structures and synthesis of the A-ring phosphine oxide synthon and the drug ED-71 (eldecalcitol) in J. Am. Chem. Soc . (2001, 123, 3716–3722) are not correct. We made revisions of their structures and developed a new synthetic route to the A-ring phosphine oxide and ED-71.